Design and optimization of thin‐film tungsten (W)‐diamond target for multi‐pixel X‐ray sources. Issue 8 (31st May 2022) - Tan, Yuewen; Chen, Qinghao; Zhou, Shuang; Henriksen, Erik A.; Zhang, Tiezhi
Abstract: Background: Emerging multi‐pixel X‐ray source technology enables new designs for X‐ray imaging systems. The power of multi‐pixel X‐ray sources with a fixed anode is limited by focal spot power density. Purpose: The purpose of this study is to optimize the W‐diamond target and predict its performance in multi‐pixel X‐ray sources. Methods: X‐ray intensity and energy deposition in the W‐diamond target with different thicknesses of tungsten film and incident electron energies was calculated with the Geant4 Monte Carlo toolkit. COMSOL Multiphysics software was used to analyze the transient and stationary heat transfer in the thin‐film W‐diamond target. The maximum tube power and X‐ray output intensity were predicted for both transmission and reflection target configurations. Results: The maximum focal spot power density was limited by either the graphitization of the diamond substrate or the melting point of the W target. With optimal W‐target thickness, the maximum transmission X‐ray intensities are about 40%–50% higher than the maximum reflection intensities. Thin‐film W‐diamond targets allow four to five times more maximum power input and produce six to seven times higher transmission X‐ray intensity in continuous mode compared with conventional reflection W thick targets. Depending on the focal spot size, reducing the X‐ray pulse duration can further enhance the tube power. Conclusions: Multi‐pixel X‐ray sources using this W‐diamond target design can produce significantly higher X‐ray output than traditional thick tungsten targets without major modification of the tube design.